The relationship between the dietary index based Meiji nutritional profiling system for adults and lifestyle-related diseases: a predictive validity study from the National Institute for Longevity Sciences—Longitudinal Study of Aging - Yu, Tao; Zhang, Shu; Wakayama, Ryota; Horimoto, Tomohito; Tange, Chikako; Nishita, Yukiko; Otsuka, Rei (Frontiers in Nutrition, 2024)
Background Nutritional profiling system (NPS) holds promise as a public health tool for companies to measure product healthiness and for individuals in making healthier food choices. The Meiji NPS for adults specifically targets lifestyle-related diseases prevalent among Japan’s adult population, including overweight/obesity, hypertension, diabetes, and dyslipidemia. This study examined the cross-sectional association between the Meiji NPS for adults Dietary Index (MNfA-DI) and indicators of lifestyle-related diseases in a population. Methods The study comprised 1,272 middle-aged individuals (40–64 years, 50.1% male) who participated in the seventh wave (2010–2012) of the National Institute for Longevity Sciences—Longitudinal Study of Aging project, with no missing data on three-day dietary records. The MNfA-DI was computed at the individual diet level (accounting for the whole diet) using arithmetic energy-weighted means. A higher MNfA-DI indicated a greater nutritional quality of an individual’s overall diet. Lifestyle-related disease indicators included body mass index (BMI, kg/m2), body fat (%), systolic and diastolic blood pressure (mmHg), fasting plasma glucose (mg/dL), HbA1c (%), triglyceride levels (mg/dL), LDL, and HDL cholesterol levels (mg/dL). A multiple regression model was used to assess the association between the MNfA-DI and lifestyle-related disease indicators, adjusting for demographics, socioeconomic status, lifestyle factors, disease history, and energy intake as covariates, depending on the outcome. Results The median (interquartile range) age and MNfA-DI were 53.0 (46.0, 59.0) years and 10.1 (6.0, 14.0) points, respectively. MNfA-DI was negatively associated with body fat [partial regression coefficient (95% confidence interval) −0.04 (−0.07, −0.01)], diastolic blood pressure [−0.08 (−0.17, −0.002)], fasting plasma glucose [−0.18 (−0.33, −0.01)], and triglyceride [−1.36 (−2.16, −0.55)]. Additionally, MNfA-DI was also associated with almost indicators (except for LDL and HDL cholesterol) among participants with a BMI between 18.5 and 24.9 kg/m2. Conclusion These findings suggest that the Meiji NPS for adults could be associated with a lower risk of lifestyle-related diseases. In addition, from a public health nutrition perspective, the Meiji NPS for adults may be useful to assess the food healthiness of the adult population.